2015
DOI: 10.1002/ptr.5512
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Verbascoside in Neuropathic Pain Induced by Chronic Constriction Injury in Rats

Abstract: We examined the effects of verbascoside in rats subjected to chronic constriction injury (CCI). Verbascoside (50, 100, and 200 mg/kg, i.p.), was administered from the day of surgery for 14 days. Spinal cord levels of apoptotic factors and glia markers were quantified on days 3, 7, and 14 post-CCI. Oxidative stress markers were assessed on days 7 and 14. CCI rats exhibited a marked mechanical allodynia, cold allodynia, and thermal hyperalgesia on days 3, 5, 7, 10, and 14 post-CCI. A significant increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…It has been reported elsewhere that MDA levels increased proportionally in relation to a decrease in the paw pain threshold (20), while Cetin et al (25) observed that MDA decreased in paw tissue with a corresponding increase in pain threshold. In another study, MDA was shown to increase in the presence of neuropathic pain (26). In support of the findings in the aforementioned studies, in the present study, an increase was also recorded in the level of MDA in the paw tissue of rats to whom paclitaxel was administered.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported elsewhere that MDA levels increased proportionally in relation to a decrease in the paw pain threshold (20), while Cetin et al (25) observed that MDA decreased in paw tissue with a corresponding increase in pain threshold. In another study, MDA was shown to increase in the presence of neuropathic pain (26). In support of the findings in the aforementioned studies, in the present study, an increase was also recorded in the level of MDA in the paw tissue of rats to whom paclitaxel was administered.…”
Section: Discussionsupporting
confidence: 92%
“…Calycosin glycoside could inhibit the cleavage and activity of caspase-3 and enhance the phosphorylation of PI3K p85 and Akt 18 . Verbascoside could decrease the expression of Bax while increasing the expression of Bcl-2 19 . All the main components may work together to synergistically inhibit the apoptosis of motor neurons in SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 93%
“…For example, icariin directly inhibited interleukin-1 receptor-associated kinase and then downregulated NF-κB expression and inflammatory cytokines secretion (such as TNF-α and interleukins) 33 . Verbascoside could increase the phosphorylation of src homology region 2 domain-containing phosphatase-1 (SHP-1) by reducing the activation of transforming growth factor β-activated kinase-1/JNK/activator protein 1 signaling, which would lead to the reduction in the expression of inflammatory cytokines and the activation of microglia 19 , 36 . P-glycoprotein (P-gp) as a membrane-bound protein is expressed in the blood side membrane of endothelial cells, and it can expel substances out of cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…As a form of programmed cell death, apoptosis was reported to be associated with the development of NP (Amin et al, 2016; Zheng et al, 2017). Caspases and Bcl-2 family proteins, including the pro-apoptosis protein Bax and the pro-survival protein Bcl-xl, play a pivotal role in cell survival and death (Cheng et al, 1997).…”
Section: Discussionmentioning
confidence: 99%